2007
DOI: 10.1053/j.gastro.2007.08.074
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and Genetic Alterations in Netrin-1 Receptors UNC5C and DCC in Human Colon Cancer

Abstract: Background & Aims-DCC and UNC5C, Netrin-1 dependence receptors, perform an important role in intestinal epithelial biology. Both receptors frequently are down-regulated in colorectal cancer (CRC). Although CRCs frequently lose DCC owing to deletions at 18q, the mechanism for the UNC5C loss is poorly understood. We hypothesized that UNC5C is silenced epigenetically in CRC, and that there are interactions between losses of UNC5C and DCC in colorectal tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
75
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 44 publications
9
75
0
1
Order By: Relevance
“…Along this line, DCC was proposed in the early 1990s to be a tumor-suppressor gene, whose expression is lost in the vast majority of human cancers (10,11). This hypothesis also fits with the observation that UNC5H genes are down-regulated in the vast majority of colorectal tumors, hence suggesting that the loss of UNC5H genes represents a selective advantage for tumor development (12)(13)(14). Interestingly, in mice, both inactivation of UNC5H3 and overexpression of netrin-1 in the gastrointestinal tract are associated with intestinal tumor progression (13,15), hence demonstrating per se that loss of netrin-1 dependence receptors in the human pathology is a causal factor for tumor progression (16).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Along this line, DCC was proposed in the early 1990s to be a tumor-suppressor gene, whose expression is lost in the vast majority of human cancers (10,11). This hypothesis also fits with the observation that UNC5H genes are down-regulated in the vast majority of colorectal tumors, hence suggesting that the loss of UNC5H genes represents a selective advantage for tumor development (12)(13)(14). Interestingly, in mice, both inactivation of UNC5H3 and overexpression of netrin-1 in the gastrointestinal tract are associated with intestinal tumor progression (13,15), hence demonstrating per se that loss of netrin-1 dependence receptors in the human pathology is a causal factor for tumor progression (16).…”
supporting
confidence: 64%
“…Thus, as predicted by the dependence receptor model, we have now shown that a tumor cell can escape receptor dependency in at least three ways. First, expression of the dependence receptor can be down-regulated, as extensively described for DCC and more recently for UNC5H (10,(12)(13)(14)21). Second, the downstream death signaling can be shut down.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of 18q chromosomal region has been correlated with poorer survival rate in stage II CRCs 69 . The region carrying the deleted in colorectal cancer gene (a dependence factor) is more frequently lost in advanced cancers 70 .…”
Section: Mutational Landscape In Chromosomal Instabilitymentioning
confidence: 99%
“…UNC5C is indeed the most downregulated member of the UNC5H family (74-77% of cases, A new paradigm in cell signaling and cancer therapy D Goldschneider and P Mehlen whereas UNC5H1/UNC5A and H2/B show a reduced expression in 48 and 27% of the cases, respectively). This loss of expression observed in human primary tumors, as well as in cell lines, is essentially due to promoter methylation (Bernet et al, 2007;Shin et al, 2007). Furthermore, Bernet and colleagues took advantage of a natural UNC5H3 loss-of-function occurring in mice (rcm, rostral cerebellar malformation) to demonstrate that UNC5H3 loss of function is associated with tumor progression: mice that carry the APC 1638N germline mutation, known to predispose mice to the development of low-grade adenoma (Sieber et al, 2000), and are heterozygous or homozygous for mutant UNC5H3, develop adenomas that progress to adenocarcinoma at a higher frequency than what is seen in APC 1638N mice.…”
Section: Drs Are Altered During Tumor Progressionmentioning
confidence: 99%